An Analysis of the Ijtihad and Thought of Abdullah Ahmed An-Na'im - Rosyadi, Ahmad; Salikin, Adang Djumhur (Multidiscience : Journal of Multidisciplinary Science, 2025)
As a mechanism for renewing Islamic law, Ijtihad becomes crucial in facing contemporary challenges. Abdullah Ahmed An-Na'im offers a progressive perspective on ijtihad, especially in the context of Islamic law reform and human rights. This research aims to analyze An-Na'im's model of ijtihad to understand his approach and its implications for contemporary Islamic law. The research method used is library research by analyzing An-Na'im's works, including books and journal articles, and secondary sources that discuss his thoughts. The data were analyzed descriptively and critically to reveal An-Na'im's method of ijtihad, its theological basis, and its relevance to modern Islamic law. The results show that An-Na'im's ijtihad is rooted in the methodology of evolutionary renewal, inspired by Mahmoud Muhammad Taha's theory of naskh. An-Na'im emphasizes the reinterpretation of Meccan period verses of the Qur'an, which are considered more universal and in line with human rights values. His approach encourages critical reflection on traditional sharia and emphasizes the principles of equality, freedom of religion, and tolerance. An-Na'im also adopts a hermeneutical and anthropological approach to interpreting the Qur'an, emphasizing the dynamic relationship between scripture, Islamic tradition, and human experience. According to him, the transformation of sharia must be open, adaptive, and inclusive of socio-cultural changes and the global environment.